THE REGIMES OF THE REALIZATION OF DESUBLIMATION METHOD FOR ULTRADISPERSE POWDER PRODUCTION - Kazenova Aykerim; Brener Arnold; Golubev Vladimir Grigorievich; Shapalov Shermakhan; Tortbayeva Dinara Ryskulbekkyzy; Kenzhalieva Gulmira; Gregory Ivahnuk (Academic Scientific Journal of Chemistry, 2019)
The paper deals with the investigation of the method of obtaining the ultrafine powders by the desublimationprocess. In the course of the experiments, the effect of temperature, pressure, and degree of supersaturation on the process kinetics and the dispersion size distribution function was investigated.The existence of the stage of the phenomenon of multiple coagulation with a high concentration of nucleates in a supersaturated vapor-gas mixture has been experimentally confirmed. Namely, it was established that with a large initial supersaturation, when a large number of embryos (monomers) of the dispersed phase are rapidly formed per unit volume of the apparatus, the contribution of multiparticle collisions is great. The obtained data may be very important for working out the engineering method for calculating and optimizing the regimes of aggregation processes to create highly homogeneous stable nanodispersions.